2018
DOI: 10.1177/1055665617739731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Distance of Maxillary Advancement on Horizontal Relapse After Orthognathic Surgery

Abstract: Our data suggest positive correlation between amount of maxillary advancement and horizontal relapse as well as a positive correlation between history of cleft and horizontal relapse. Bone grafting of the maxillary osteotomy sites has a protective effect on the relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 33 publications
(42 reference statements)
2
38
1
Order By: Relevance
“…This rate was much higher than the rates for LFI with rigid fixation with interpositional bone grafting. The results of this review are in agreement with the conclusions drawn by Fahradyan et al through a multiple linear regression analysis, who reported that bone grafting at maxillary osteotomy sites has a positive effect on relapse 36 .…”
Section: Bone Grafting In Lfi With Rigid Fixationsupporting
confidence: 92%
See 3 more Smart Citations
“…This rate was much higher than the rates for LFI with rigid fixation with interpositional bone grafting. The results of this review are in agreement with the conclusions drawn by Fahradyan et al through a multiple linear regression analysis, who reported that bone grafting at maxillary osteotomy sites has a positive effect on relapse 36 .…”
Section: Bone Grafting In Lfi With Rigid Fixationsupporting
confidence: 92%
“…The characteristics of the selected studies are presented in Table 1. Collectively, these 24 studies included 570 eligible patients: group A (15 studies, 405 eligible patients 4,14,15,18,21,[36][37][38][39][40][41][42][43][44][45] ); group B (10 studies, 126 eligible patients 14,18,21,26,35,[46][47][48][49][50] ); and group C (two studies, 39 eligible patients 30,33 ). Three of the studies were included in both group A and group B 14,18,21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After orthognathic surgery, cleft patients have a higher than normal risk of relapse due to factors such as different soft tissue-bone relations and complex mobilization vectors. Fahradyan et al [59] reported that, in comparison to class III malocclusion patients without clefts, more relapse was encountered in those with Orthognathic Surgery in Cleft Lip and Palate Patients DOI: http://dx.doi.org/10.5772/intechopen.89556 clefts (1.25 mm or more on average), and there was a significant positive correlation between larger clefts and horizontal relapse. In their study, the mean relapse rate was similar among different types of clefts, and in the case of each 1 mm increase in maxillary advancement, horizontal relapse increased by 0.3 mm on average [59].…”
Section: Success Of Orthognathic Surgerymentioning
confidence: 99%